Diplomasi Budaya Prancis Melalui Alliance Francaise di Indonesia 2011-2021 - Vernina Dewi, Luh Gede Merlia; Kumala Dewi, Putu Ratih; Parameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
French cultural diplomacy through the Alliance Francaise has undertaken several activities to increase the spread of French culture in Indonesia. France considers Indonesia as a country that has the potential to collaborate and spread French language and culture. The spread of French culture through language is carried out by people to people, in other hand there have been several attempts by the French government to spread French culture through AF. This study then aims to understand the efforts of the French government to spread French culture in Indonesia from 2011 to 2021 using qualitative methods. This research refers to the theory of cultural diplomacy and second track diplomacy. This study found that French cultural diplomacy through AF can bring a positive French image and introduce French culture through language, film festival screenings and music. the target audience of the French cultural diplomacy program through AF is citizens or groups of individuals, but cultural diplomacy itself is funded, designed and delivered by the French government. AF indirectly contributes to the spread of French culture in Indonesia.